Implementasi Prinsip Pendidikan Orang Dewasa pada Pelatihan Tata Busana di Satuan Pendidikan Non Formal SKB Ungaran - Rana Indah Setiawati; Imam Shofwan (Lifelong Education Journal, 2023)
Training and courses play a vital role in training qualified human resources, yet many adult education programs still overlook learning quality. Based on this, interactive learning in accordance with adult education principles is required. The purpose of this study is to discover: (1) the implementation of self-concept in fashion training; (2) the implementation of learning experiences in fashion training; (3) the implementation of learning readiness in fashion training; and (4) the implementation of adult learning orientation in clothing design training. This study is a descriptive qualitative study that collected data by monitoring the execution of Clothing Design training activities, conducting interviews regarding learning activities with a number of LCS heads, two instructors, and five training students. Modules, lesson plans, and training implementation reports are all necessary documents. The validity of the data is determined through source triangulation (interviews, documents, and observations), and data analysis techniques are used to acquire data, reduce data, present data, and make conclusions. This study's findings include: (1) Self-concept implementation: trainees are not directly involved in the learning planning process, but they do participate in agreements during the learning process and at the evaluation stage. (2) Learning experience implementation: project-based learning is applied in the Ungaran SKB. (3) Learning readiness implementation: adult learning at SKB Ungaran is relevant to trainees' vocations and lives. (4) Learning orientation implementation: trainees receive adequate encouragement from the teacher when they encounter difficulties in learning. This study concluded that adult learning implementation must apply adult principles by incorporating students in learning, designing learning that emphasizes experimental principles, adapting learning that can be directly applied, and having a learning orientation. The benefit of this research is knowing how to apply learning in accordance with adult learning principles.